Revitalization of Multicultural Islamic Education Within the Family in The Modern Era - Huda , Miftahul; Asiah , Siti; Rahim , Ahmed H al- (Al-Insyiroh: Jurnal Studi Keislaman, 2022)
This essay seeks to evaluate multicultural Islamic religious education in the home, examine the issues of multicultural Islamic religious education in contemporary Indonesia, and Identify the modern family's rejuvenation of multicultural Islamic religious education This paper employs phenomenological qualitative methodology using a random sample procedure. Utilized data collecting methods include interviews, observation, and documenting. Multicultural Islamic religious education in the family can be applied in Islamic households that accept religious differences and diversity, equality, justice, togetherness, peace, and respect for cultural diversity both within and outside the family. Multicultural Islamic religious education in the family can be applied in Islamic households that accept religious differences and diversity, equality, justice, togetherness, and peace. The challenges facing multicultural Islamic religious education in the modern era are the level of multicultural Islamic religious education that has not yet reached its maximum level and the diminishing sense of national identity among the future generation, particularly among school-aged children. Ways to revitalize multicultural Islamic religious education in the family in the modern era are: inclusive attitude in life; parental control in providing awareness, enlightenment, empowerment, and role model for children to wisely use the internet or social medias to become a complete human being; parents emphasizing the moral aspect in educating their children; parents instilling values character in children that come from religion, Pancasila, culture, and Indonesia; and parents emphasizing the moral aspect in educating